Antimicrobial and antioxidant activity of various solvent extracts of Salsola stenoptera Wagenitz and Petrosimonia nigdeensis Aellen (Chenopodiaceae) plants - Meltem Asan Ozusaglam" (Science Faculty of Chiang Mai University, 2019)
This study was conducted to examine the in vitro antimicrobial and antioxidant activities of various extracts (ethanol, methanol, n-hexane, dicholoromethane and water) prepared from the stem and leaf+fruit of Salsola stenoptera Wagenitz and Petrosimonia nigdeensis Aellen (Chenopodiaceae) plants. The antimicrobial activities of the plant extracts were tested according to agar well diffusion and microdilution broth methods. The extracts showed a strong antimicrobial activity and a broad antimicrobial spectrum for all tested microorganisms. Minimal bactericidal (MBC) or fungicidal (MFC) concentrations for microorganisms which were sensitive to the stem and fruit+leaf extracts of S. stenoptera and P. nigdeensis in the agar well diffusion assay were in the range of 5.63-180.00 mg/mL and 11.25-180.00 mg/mL, respectively. The extracts were also subjected to screening for their possible antioxidant activity with scavenging activity of DPPH radicals, hydrogen peroxide scavenging activity and chelating ability on ferrous ions. All tested extracts showed varying degrees of efficacy in each assay in a dose-dependent manner. In general, polar extracts exhibited stronger activities than non-polar extracts. The ethanol and n-hexane extracts of S. stenoptera and P. nigdeensis stem showed the highest scavenging abilitiy on DPPH radicals with the IC50 values of 29.84 µg/mL and 83.56 µg/mL, respectively. The total phenolic and flavonoid contents were also determined. The highest gallic acid equivalents (GAE) and quercetin equivalents (QE) values, for both plants, were 44.78 μg GAE/mg and 66.69 μg QE/mg, respectively. The results indicate that both plant species may have health benefits as sources of natural antioxidants and antimicrobial agents for use in functional foods and/or in pharmaceutical industry.